Datasets of the solar quiet (Sq) and solar disturbed (SD) variations of the geomagnetic field from the mid latitudinal Magnetic Observatory of Coimbra (Portugal) obtained by different methods - Morozova, Anna L. (2021)
to be submitted to Data in Brief